"Psychological Factors Influencing Injury Rehabilitation and Return to Sport: A Systematic Review" - Andre Frank; George Oscar, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The essential purpose of this research study is to determine the psychological factors influencing injury rehabilitation also the return to sport. This research study depends upon primary data analysis to determine whether the research used SPSS software and generated informative results related to them. The research describes the systematic review to determine the research used descriptive statistic analysis, correlation coefficients, and regression analysis; it also explains the ANOVA model between psychological factors and injury rehabilitation and sports return. Remember that each individual's return-to-sport schedule and procedure will vary based on the nature and severity of the injury, as well as individual circumstances. Consulting with a healthcare specialist and working closely with a competent sports rehabilitation team can help you design a specific strategy for a safe and successful return to sport. The overall research study found that there are positive and significant influence psychological factors in injury rehabilitation.